South East Asia in the world-economy - Dixon, Chris (Cambridge University Press, 1991)
This is the first textbook survey of the pivotal position occupied by Southeast Asia in both the wider Asian and international economy. Professor Chris Dixon demonstrates how Southeast Asia's role has undergone frequent and profound change as a result of the successive emergence and dominance of mercantile, industrial and finance capital. He shows how the region has developed as a supplier of luxury products, such as spices; as a producer of bulk primary products; and how, since the 1960s, it has become a major recipient of investment and a favored location for labor-intensive manufacturing operations. The author examines how this progressive integration of South East Asia in the world economy has established the dominance of a small number of core areas and, in a concluding chapter, he explores the way in which the restructuring of the world economy in the 1980s has opened Southeast Asia to a new cycle of capitalist penetration.